Evaluating the sensory properties of unpolished Australian wild rice. (January 2018) - Tikapunya, Tiparat; Henry, Robert J.; Smyth, Heather
Abstract: Australian wild rices are genetically distinct from commercially cultivated rices and present new opportunities for the development of improved rice cultivars. Before use in rice breeding, the eating and cooking properties of Australian wild rice must first be understood as these are key factors in determining rice quality and consumer acceptance. Samples of Australian wild rice (taxa B) were collected and evaluated together with a commercial Canadian wild rice ( Zizania aquatic L.), Oryza sativa L.cv. Nipponbare, and selected commercial rices including long grain, medium grain, basmati, red basmati, and red rice. Cooking profiles were established, physical traits were measured and conventional descriptive analysis techniques were used to compare the sensory properties of the unpolished rices. Twenty six descriptors, together with definitions, were developed with a panel of twelve experienced assessors including aroma, flavour, texture and aftertaste attributes. Results reveal that the Australian wild rice had a mild aroma and flavour similar to that of red rice and red basmati but without the lingering aftertaste. In terms of texture, the wild rice was firmer, and somewhat crunchy and chewy rather than soft and fluffy despite requiring a longer cooking time. The sensory, physical and cooking profiles indicate that Australian wild rice has a high potential for commercialization in itself and provides a suitable genetic source for breeding programs, particularly in the coloured rice market. Graphical abstract: Highlights: The longer cooking time required the higher the firmness score for cooked unpolished rice due to bran layer characteristics. Undesirable sensory attributes of cooked unpolished rices has a strong correlation to the presence of red bran layers. Australian wild rice (with a mid-red bran layer) has an acceptable eating quality similar to commercial brown rice. Commercial and novel Australian wild rices each exhibit unique sensory properties.